2022
DOI: 10.1161/atvbaha.122.317746
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Complement Activating Enzyme MASP-2 Are Associated With the Risk of Future Incident Venous Thromboembolism

Abstract: BACKGROUND: Experimental studies have shown that the complement activating enzyme MASP-2 (mannose-binding lectin associated serine protease 2) exhibits a thrombin-like activity and that inhibition of MASP-2 protects against thrombosis. In this study, we investigated whether plasma MASP-2 levels were associated with risk of future venous thromboembolism (VTE) and whether genetic variants linked to MASP-2 levels were associated with VTE risk. METHODS: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Genomic and proteomic dysregulation of lectin proteases exacerbate the disease consequences as upregulation of MASP-1, 2, and 3 eventually increases the embolism possibility [78,79]. Upregulation of lectin pathway-associated proteins predisposes towards autoimmune disease susceptibility such as Hashimoto's thyroiditis [80] and Systemic Lupus Erythematosus (SLE) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and proteomic dysregulation of lectin proteases exacerbate the disease consequences as upregulation of MASP-1, 2, and 3 eventually increases the embolism possibility [78,79]. Upregulation of lectin pathway-associated proteins predisposes towards autoimmune disease susceptibility such as Hashimoto's thyroiditis [80] and Systemic Lupus Erythematosus (SLE) [26].…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72][73][74] According to the study by Damoah et al, having elevated levels of the complement-activating enzyme Masp-2 raises the chance for developing venous thromboembolism in the future. 75 Furthermore, the absence of B cells in mice indirectly contributes to venous thrombosis by elevating neutrophil counts and increasing fibrinogen levels. The inferior vena cava (IVC) stenosis model demonstrated an augmented incidence of venous thrombosis due to B-cell deficiency, which was hypothesized by investigators to be caused by a rise in circulating neutrophils leading to an increased abundance of NETs within the thrombus and upregulation of fibrinogen production.…”
Section: Immunological Mechanism Of Venous Thrombosismentioning
confidence: 99%
“…15 Epidemiological studies have found high plasma levels of complement factors MASP2, C3, and C5 to be associated with an increased risk of VTE. [16][17][18] Importantly, patients with HAE typically have low plasma levels of functional complement factor C4, likely caused by aberrant activation of the complement system and consumption of this factor. 19 The advent of C1INH replacement therapies, including purified plasma C1INH and recombinant C1INH preparations, represented an important advance in the treatment of patients with HAE.…”
Section: Hereditary Angioedema Is Associated With An Increased Risk O...mentioning
confidence: 99%